Are children more vulnerable to mesothelioma than adults? A comparison of mesothelioma risk among children and adults exposed non-occupationally to blue asbestos at Wittenoom. Issue 12 (29th August 2018) - Reid, Alison; Franklin, Peter; Berry, Geoffrey; Peters, Susan; Sodhi-Berry, Nita; Brims, Fraser; Musk, Arthur William; de Klerk, Nicholas H
Abstract : Objectives: The presence of asbestos in public buildings is a legacy of past asbestos use in many developed countries. Of particular concern is the amount and current condition in schools and the vulnerability of children to mesothelioma. Our aim was to compare the risk of mesothelioma between those exposed to blue asbestos as children and as adults at Wittenoom. Methods: Public sources were used to establish the Wittenoom residents' cohort. Mesothelioma incidence rates per 100 000 person-years at risk were derived for those first exposed to asbestos at Wittenoom as children (<15 years) or adults separately. Proportional hazards survival models examined the slope of the exposure-response relationship between asbestos exposure and incidence of mesothelioma in different sex and age groups. Results: The mesothelioma rate was lower among those first exposed as children (76.8 per 100 000) than those first exposed as adults (121.3 per 100 000). Adjusting for cumulative exposure to asbestos and sex, those exposed as adults had a greater risk of mesothelioma (adjusted HR 2.5, 95% CI 1.7 to 3.7). The slope of the exposure-response relationship did not differ between those exposed as children and those exposed as adults. Conclusion: We found no greater susceptibility to mesothelioma among those first exposed to asbestos as children than those first exposed as adults. However, given the long latency of mesothelioma, and the greater years of life yet to be lived by the Wittenoom children, it is likely that there will be more cases of mesothelioma in the future among those first exposed as children.